2021
DOI: 10.1101/2021.11.18.21266442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunoglobulin G1 Fc glycosylation as an early hallmark of severe COVID-19

Abstract: BackgroundImmunoglobulin G1 (IgG1) effector functions are impacted by the structure of fragment crystallizable (Fc) tail-linked N-glycans. Low fucosylation levels on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein specific (anti-S) IgG1 has been described as a hallmark of severe coronavirus disease 2019 (COVID-19) and may lead to activation of macrophages via immune complexes thereby promoting inflammatory responses, altogether suggesting involvement of IgG1 Fc glycosylation modulate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(39 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…2B patients, as previously described (Fig. 2B) (2,30). A high level of IgG galactosylation boosted the classical complement pathway activation capacity through enhanced C1q-binding, which was in line with previous reports (Fig.…”
Section: Bnt162b2 Mrna Vaccination Induces Transient Afucosylated Ant...supporting
confidence: 92%
See 3 more Smart Citations
“…2B patients, as previously described (Fig. 2B) (2,30). A high level of IgG galactosylation boosted the classical complement pathway activation capacity through enhanced C1q-binding, which was in line with previous reports (Fig.…”
Section: Bnt162b2 Mrna Vaccination Induces Transient Afucosylated Ant...supporting
confidence: 92%
“…Anti-S IgG Abs were affinity-captured from plasma or sera using recombinant, in-house produced trimerized spike protein-coated plates (Thermo Fisher Scientific, Roskilde, Denmark) followed by a 100 mM formic acid elution step, as described elsewhere (2,49). Total IgG Abs were affinity-captured from plasma or sera using a Protein G AssayMAP Cartridge Rack on the Bravo (Agilent Technologies, Santa Clara, CA) or Protein G Sepharose 4 Fast Flow beads (GE Healthcare, Uppsala, Sweden) in a 96-well filter plate (Millipore Multiscreen, Amsterdam, Netherlands), respectively, as described elsewhere (2,30,52).…”
Section: Igg Fc Glycosylation Analysis By Mass Spectrometrymentioning
confidence: 99%
See 2 more Smart Citations
“…Antibody effector functions are highly affected by the composition of the N-glycan present at the conserved N-glycosylation site in the Fc region (60,61,(87)(88)(89). Hitherto, it has been repeatedly shown that disease-specific antibodies can exhibit skewed glycosylation profiles, that in turn associate with disease prognosis and outcome (73,(90)(91)(92)(93). Historically, one of the key limitations of glyco-profiling such antibodies is their low serum prevalence and high sample requirement.…”
Section: Discussionmentioning
confidence: 99%